Aestheticization of female body: Narrative Intrusion of the Unnecessary Description in The God of Small Things by Arundhati Roy - Ansar, Mohammed; Hussain, Makhdoom (Educalitra: English Education, Linguistics, and Literature Journal, 2025)
This paper examines the aesthetics of the female body in Arundhati Roy’s The God of Small Things (1997), through the intrusive descriptions of its surface. Drawing on Gérard Genette ‘s concept of ‘focalization,’ it analyses how Roy’s narrative voice navigates the representation of female characters, their bodies and the politics of gender and power wherein these representations operate. The study contends that although such descriptions seems overemphasized it is a technique that brings out objectification and commodification of women in a patriarchal society. By identifying the difference between external focalization (the position of the observer) and internal focalization (that of the character), the paper deconstructs the vanity of aestheticization and an ideological reading. This paper aims to investigate aestheticization of the female body in Roy’s novel by asking how such descriptions can be considered as a type of narratorial interruption when they seem to go beyond the need of the story or characterization. Hence, this literary analysis engages with the current discussions of feminist literary criticism as it relates to narrative form, gender politics and, or, the representation of subjects in contemporary literature.